Some Threatened Medicinal Plants of Rajasthan and their Conservation - Billore, K. V. (Indian Forester, 1989)
The present day fast developments in the society has brought about substantial depletion of natural resources, particularly the forests, which infact are the main source of vegetable drugs. The forests of Rajasthan are also in the state of denudation and thereby imposing threat to a number of medicinal plants. A need for conservation of medicinal plant has been realised in the recent Past. In the present paper a preliminary analysis of threatened medicinal plants and the problem of conservation of medicinal plants has been discussed.